The role of artificial intelligence in enhancing administrative decision support systems by depend on knowledge management - Hasanain Abdalridha Abed Alshadoodee; Muneer Sameer Gheni Mansoor; Hasanien Kariem Kuba; Hassan Muwafaq Gheni (Bulletin of Electrical Engineering and Informatics, 2022)
This study illustrates the role of artificial intelligence in enhancing administrative decision support systems by depend on knowledge management. As per new technologies are evolving and the workflow need more concious approach of implementation, thus the role of artificial intelligence is evolved in support to decision making. The study takes privates college administration as a varible on which the results rely. The upgrades in innovation have upgraded most techniques for leading business tasks that further develop organizations and administration conveyance. Companies in this area need to wander into digitizing of all industry cycles, business sequences linked to administration and more essential services in educational institutes over time. The need for a proper decision-making support using knowledge management stills create a big gap in the foundation of an effective and efficient eductaional system for the good governance and to improve the image of some institute. The examination interaction has been intended to follow an iterative methodology of information revelation chose for the review. Using the statistical package for social sciences (IBM-SPSS) version 23 logic instrument, the illustrative research was completed with insights into the segment profile of the respondents. Hayes' process macro v3.3 with SPSS was used to analyze the interceding effect.